Potensi Limbah Sisik Ikan Sebagai Kitosan dalam Pembuatan Bioplastik - Ajeng Ayu Ramadhani; Nirmala Fitria Firdhausi (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2021)
Bioplastics are environmentally friendly plastics derived from natural materials. Bioplastics are easier to decompose when compared to commercial plastics. Bioplastics are generally made from starch contained in plants. But the use of starch as a base material has the disadvantage of producing bioplastics that are not waterproof. Therefore, it is necessary to add chitosan to improve bioplastic characteristics. Chitosan usually comes from the shell of crustacean animals, but it turns out that in fish scales waste, also contains chitosan. Fish scales are a by-product of the process of fish processing. Fish scales are only discarded and not utilized so that they become waste that can pollute the environment. Fish scales have a chitin content that can process into chitosan, which can be useful as an additional ingredient in the manufacture of bioplastics. This review aims to find out the potential of fish scales waste as chitosan in the manufacture of bioplastics. Based on the results of previous research, fish scales have a chitosan content that can use as an additional ingredient in the manufacture of bioplastics. Fish scale chitosan can form bioplastic film with characteristic brownish-yellow film. The addition of fish scale chitosan is also able to improve the water resistance of bioplastic film. Based on the results of the review can be concluded bring fish scales to have the potential as chitosan that can use in the manufacture of bioplastic.Keywords – Bioplastic, Chitosan, Fish Scales.